2014
DOI: 10.4252/wjsc.v6.i4.505
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of stem cells from human exfoliated deciduous teeth for bone regeneration in the dog mandibular defect

Abstract: SHEDs which had been isolated and characterized 5 years ago and stored with cryopreservation banking were capable of proliferation and osteogenesis after 5 years, and no immune response was observed after three months of seeded SHEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 23 publications
1
39
0
2
Order By: Relevance
“…Recently, it was shown that both DPSCs and SHED combined with Platelet-Rich Plasma (PRP) were able to regenerate vascularized bone tissue around dental implants in dog and puppy models, respectively [55]. Recent reports have also shown that 5-year cryopreserved SHED were still able to proliferate and undergo osteogenesis without immune reaction in a 9 mm mandibular defect in dogs [94] and to enhance mandibular distraction osteogenesis in a rabbit model [95]. …”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%
“…Recently, it was shown that both DPSCs and SHED combined with Platelet-Rich Plasma (PRP) were able to regenerate vascularized bone tissue around dental implants in dog and puppy models, respectively [55]. Recent reports have also shown that 5-year cryopreserved SHED were still able to proliferate and undergo osteogenesis without immune reaction in a 9 mm mandibular defect in dogs [94] and to enhance mandibular distraction osteogenesis in a rabbit model [95]. …”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%
“…Subsequently, several studies were performed to identify other sources and to understand how these cells can give rise to distinct cell types, for the purpose of using these cells in regenerative procedures [39][40][41][42][43] . In this context, dental tissues have also been investigated as niches of MSCs, and many toothderived SCs (TDSCs) have been identified and characterized, including dental pulp SCs (DPSCs) [44][45][46][47][48] , SCs from human exfoliated deciduous teeth (SHED) [49][50][51][52][53] , periodontal ligament SCs (PDLSCs), dental follicle progenitor cells (DFPCs) [54][55][56] , SCs from apical papilla (SCAP) [19,[56][57][58][59] , and periodontal ligament of deciduous teeth SCs (DePDL) [50,51,[60][61][62] (Figure 1). Dental tissues are an accessible source of MSCs that can be obtained with limited morbidity and without additional risks to the donor, as extracted/exfoliated teeth represent a waste product of dental procedures [13,[63][64][65] .…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells (SCs) are an increasing subject once they are a way to regenerate injured tissues and should improve the treatment of some illness that so far has no resolution such as diabetes and Parkinson's disease. They can be obtained [8][9][10][11][12] , exfoliated deciduous teeth [13][14][15][16][17] , periodontal ligament, dental follicle [18][19][20] , apical papilla [21][22][23][24] , periodontal ligament of deciduous teeth [14][15][25][26][27] and gingival tissue stem cells 28 . This review article proposes to summarize the literature regarding the current knowledge about stem cells from dental tissue, and their potential in regenerative therapy.…”
Section: Introductionmentioning
confidence: 99%